High pinning performance of YBa2Cu3O7-x films added with Y2O3 nanoparticulate defects - Mele P.; Guzman R.; Gazquez J.; Puig T.; Obradors X.; Saini S.; Yoshida Y.; Mukaida M.; Ichinose A.; Matsumoto K.; Idries Adam M. (Institute of Physics Publishing, 2023)
Barium zirconate; Epitaxial growth; Flux pinning; High resolution transmission electron microscopy; Magnesia; Nanorods; Pulsed laser deposition; Scanning electron microscopy; Strontium titanates; Superconducting films; Titanium compounds; Transmission electron microscopy; Vortex flow; Yttrium barium copper oxides; Applied magnetic fields; Artificial pinning centers; isotropic pinning; Scanning transmission electron microscopy; Single vortices; Superconducting critical temperatures; Superconducting properties; YBCO film; Copper compounds